THE CHALLENGES OF TEACHING LISTENING SKILLS TO ADULT LEARNERS - Qo’chqorova Zulfizar Abduxamid qizi; No’monjonova Durdonaxon Ilhomjon qizi; Maxmudova Odinaxon Muzaffar qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Teaching listening skills to adult learners can be a challenging task for many educators. This article aims to explore the difficulties encountered when teaching listening skills to adult learners and provide suggestions for overcoming these challenges. The article discusses six main difficulties: focusing and concentrating, limited time for study, understanding accents and dialects, applying listening skills in real-life situations, and lack of motivation and interest, aggressive listening and also scientific methods and researches.